2001
DOI: 10.1677/joe.0.1690381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adenosine 5'-triphosphate and growth hormone on cellular H+ transport and calcium ion concentrations in cloned bovine mammary epithelial cells

Abstract: The present experiment was carried out to investigate the effects of exogenous adenosine 5 -triphosphate (ATP) and growth hormone (GH) on cellular H + efflux rate (extracellular acidification rate) and Ca 2+ concentration ([Ca 2+ ] c ) in cloned bovine mammary epithelial cells (bMEC) raised from the mammary gland of a 26-daypregnant Holstein heifer. Perifusion of 2-day cultured cells with a medium containing ATP (10, 100 and 1000 µmol/l) for 30 min caused a significant and concentration-dependent increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Among these receptors, P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , and P2Y 11 couple to G q/11 and activate phospholipase C, resulting in increased inositol 1,4,5-trisphosphate formation and mobilization of intracellular Ca 2ϩ (2,5,8,12,14,15,27,29,29). In the present study, several P2Y receptor mRNA subtypes (P2Y 1 , P2Y 2 P2Y 4 , and P2Y 6 ) were identified in HME cells.…”
Section: Discussionsupporting
confidence: 53%
“…Among these receptors, P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , and P2Y 11 couple to G q/11 and activate phospholipase C, resulting in increased inositol 1,4,5-trisphosphate formation and mobilization of intracellular Ca 2ϩ (2,5,8,12,14,15,27,29,29). In the present study, several P2Y receptor mRNA subtypes (P2Y 1 , P2Y 2 P2Y 4 , and P2Y 6 ) were identified in HME cells.…”
Section: Discussionsupporting
confidence: 53%
“…In pulmonary circulation, uridine nucleotides were shown to cause comparative vasodilatation as adenine nucleotides did (Konduri et al, 2004). Activation of P2Y receptors (one of Gprotein coupled receptors) by ATP caused intracellular calcium metabolism in mammary epithelial cells (Katoh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The method for [Ca 2C ] c measurement was principally the same as that described previously for bovine mammary epithelial cells (Katoh et al, 2001). Briefly, 3-d cultured dispersed cells on a collagen-coated, glassbottomed well (35 mm o.d., Matsunami, Japan) were washed with HEPES-buffered solution (mM) (NaCl, 115; KCl, 5.4; CaCl 2 , 1.3; MgCl 2 , 1.0; NaHCO 3 , 18; glucose, 7.5; HEPES, 20; pH 7.4), incubated with Fluo-3/ AM (1 mM) for 60 min at 37 (C. The cells were washed three times with the solution, and [Ca 2C ] c of individual cells were measured using a confocal laser scanning microscope system (MRC-1024, Bio-Rad, USA) attached to an inverted microscope (Axiovert 100, Zeiss, Germany).…”
Section: Measurement Of [Camp] C and [Ca 2c ] Cmentioning
confidence: 99%